Remarks on Partnering to Address Severe Food Insecurity - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, said that this is a fundamental moral issue. The fact that tens of millions of people are at risk of starving to death is a tragedy. And in the 21st century, the fact that we haven’t ended famine is a collective failure of shameful proportions. It’s also a critical economic issue. From a human capital standpoint, famines raise child mortality, increase stunting, and impair cognitive development for children in utero at the time of the famine and of the children who survive. First, early warning must translate into early action. Investing in more proactive responses to avert humanitarian crises could save millions of lives, and it can also reduce the costs to the international community by as much as 30 percent. Second, we need sustained collective action, before, during, and after crises. Third, we need to work to develop more comprehensive approaches to famine prevention, preparedness, and early action.